A multiscale Galerkin approach for a class of nonlinear coupled reaction-diffusion systems in complex media - Muntean, Adrian; Neuss-Radu, Maria (Journal of mathematical analysis and applications, 2010)
A Galerkin approach for a class of multiscale reaction-diffusion systems with nonlinear coupling between the microscopic and macroscopic variables is presented. This type of models are obtained e.g. by upscaling of processes in chemical engineering (particularly in catalysis), biochemistry, or geochemistry. Exploiting the special structure of the models, the functions spaces used for the approximation of the solution are chosen as tensor products of spaces on the macroscopic domain and on the standard cell associated to the microstructure. Uniform estimates for the finite dimensional approximations are proven. Based on these estimates, the convergence of the approximating sequence is shown. This approach can be used as a basis for the numerical computation of the solution.
Gesehen am 17.05.2023